Sampling Protocols: Version 5 - Legacy, The Nansen (The Nansen Legacy Report Series, 2020)
The collection of detailed sampling protocols is crucial tool for the success of the Nansen Legacy, because they ensure: • Methodological agreement between the involved researchers • Continuity and comparable data throughout the 5 years sampling period • An easily accessible overview over parameters sampled • Easier cruise planning